The Effectiveness of Remittances from Migrant Workers in Overcoming Poverty in Developing Asian Countries - Farawi Ghannili; Muhammad Lucky P (Journal of Risk Analysis and Crisis Response (JRACR))
This study explores the effect of remittances on poverty in developing Asian countries. This study aims to examine the effect of remittances on poverty by developing the Swamy and Arora model. There are relative influences in understanding the effect of remittances in alleviating poverty in developing Asian countries, namely geographical location and destination country income. Identify and understand the key variables that significantly affect poverty. This paper is the first to address the risk of poverty by utilizing poor migrants to increase household consumption and reduce poverty in the country of origin. We use Generalized Least Square (GLS) and Generalized Method of Moment (GMM) models to explore and understand the conditions of the poor who are sent money by migrants. The findings reveal a significant difference between poverty as measured through consumption expenditure and the income of the remitted poor. These insights are reassuring in that remittances can increase household consumption and do little to increase the income of the poor. remittances of 5% of GDP can help in alleviating poverty conditions in the home country, and directly benefit the country's economy, and alleviate domestic policies for poverty alleviation.